Complementarities and systems: Understanding Japanese economic organization - Milgrom, Paul; Roberts, John (Estudios Económicos de El Colegio de México, 1994)
The performance of the Japanese economy in the last forty-five years, during which it has gone from post-war destitution and near collapse to one of the richest and most productive in the world is unmatched in human history. The purposes of this essay are to interpret both the characteristic features of Japanese economic organization in terms of the concept of complementarity, and some recent developments in Japanese economy, and to speculate on its future.